Shades of Anger: Reclaiming Palestinian Identity Through Decolonial Resistance (المجلة الدولية للعلوم التربوية والآداب, 2024)
The present study deals with Rafeef Ziadah’s poem Shades of Anger (2015) via decolonization theory, focusing on its engagement with colonization and resistance. Ziadah uses language, historical references, and media to address the ongoing violence marginalized communities face, asserting that spoken word poetry is a powerful tool for advocating Palestinian self-determination and cultural reclamation. Accordingly, Ziadah confronts dominant discourses emphasizing unity in the quest for justice and freedom. This study examines how Shades of Anger acts as a personal and collective form of resistance, prompts critical discussions on identity, race, and decolonization. The study inquires: ‘How does Shades of Anger resist colonial discourse and empower Palestinian identity?’ The findings suggest that Ziadah’s work articulates a transformative vision of decolonial resistance and cultural resilience, highlighting the importance of reclaiming Palestinian narratives in the face of colonial oppression.